Heart failure: preventing disease and death worldwide. (August 2014) - Ponikowski, Piotr; Anker, Stefan D.; AlHabib, Khalid F.; Cowie, Martin R.; Force, Thomas L.; Hu, Shengshou; Jaarsma, Tiny; Krum, Henry; Rastogi, Vishal; Rohde, Luis E.; Samal, Umesh C.; Shimokawa, Hiroaki; et al.
<x xml:space="preserve">Abstract</x> Heart failure is a life‐threatening disease and addressing it should be considered a global health priority. At present, approximately 26 million people worldwide are living with heart failure. The outlook for such patients is poor, with survival rates worse than those for bowel, breast or prostate cancer. Furthermore, heart failure places great stresses on patients, caregivers and healthcare systems. Demands on healthcare services, in particular, are predicted to increase dramatically over the next decade as patient numbers rise owing to ageing populations, detrimental lifestyle changes and improved survival of those who go on to develop heart failure as the final stage of another disease. It is time to ease the strain on healthcare systems through clear policy initiatives that prioritize heart failure prevention and champion equity of care for all. Despite the burdens that heart failure imposes on society, awareness of the disease is poor. As a result, many premature deaths occur. This is in spite of the fact that most types of heart failure are preventable and that a healthy lifestyle can reduce risk. Even after heart failure has developed, premature deaths could be prevented if people were taught to recognize the symptoms and seek immediate medical attention. Public awareness campaigns focusing on these messages have great potential to improve outcomes for patients with heart failure and ultimately to save lives. Compliance with clinical practice guidelines is also associated with improved outcomes for patients with heart failure. However, in many countries, there is considerable variation in how closely physicians follow guideline recommendations. To promote equity of care, improvements should be encouraged through the use of hospital performance measures and incentives appropriate to the locality. To this end, policies should promote the research required to establish an evidence base for performance measures that reflect improved outcomes for patients. Continuing research is essential if we are to address unmet needs in caring for patients with heart failure. New therapies are required for patients with types of heart failure for which current treatments relieve symptoms but do not address the disease. More affordable therapies are desperately needed in the economically developing world. International collaborative research focusing on the causes and treatment of heart failure worldwide has the potential to benefit tens of millions of people. Change at the policy level has the power to drive improvements in prevention and care that will save lives. It is time to make a difference across the globe by confronting the problem of heart failure. A call to action: policy recommendations We urge policymakers at local, national and international levels to collaborate and act on the following recommendations. Promote heart failure prevention Support the development and implementation of public awareness programmes about heart failure. These should define heart failure in simple and accessible language, explain how to recognize the symptoms and emphasize that most types of heart failure are preventable. Highlight the need for healthcare professionals across all clinical disciplines to identify patients with illnesses that increase the risk of heart failure and to prescribe preventive medications. Prioritize the elimination of infectious diseases in parts of the world where they still cause heart failure. Improve heart failure awareness amongst healthcare professionals Encourage the development and use of heart failure education programmes for all appropriate healthcare professionals. These should aim to improve the prevention, diagnosis, treatment and long‐term management of heart failure and raise awareness of clinical practice guidelines. Ensure equity of care for all patients with heart failure Provide a healthcare system that delivers timely access to diagnostic services and treatment of heart failure, as well as a seamless transition to long‐term management. Ensure that the best available and most appropriate care is consistently provided to all patients with heart failure through efficient use of resources. Support and empower patients and their caregivers Provide resources for the education and practical support of patients with heart failure and their families or other caregivers, empowering them to engage proactively in long‐term care. Promote heart failure research Fund and encourage international collaborative research to improve understanding of the patterns, causes and effects of modern day heart failure and how the disease can be prevented across the globe. Fund and encourage research into new and more affordable therapies and medical devices for all types of heart failure. Fund and encourage research into evidence‐based healthcare performance measures that reflect improved clinical outcomes for patients with heart failure.